2015
DOI: 10.1007/978-3-319-13117-7_69
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-Motor Interaction in the Estimation of Distance: Athletes vs. No-Athletes

Abstract: To build a representation of the space surrounding us with an appropriate perceptual precision, our brain has to obtain the distance information from a variety of cues that are present in the scene. But these data are affected in some way by our self-motion perception. Using an indirect method of distance estimation, we investigated the effect of the visuo-motor interactions on the perception of distance in two groups of observers, one of athletes and other of no-athletes. The results showed a difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Two experiments used comparable distance measures, but in athletic populations ( Asaf, Santillán & Barraza, 2015 ; Jarraya et al, 2013 ). Asaf, Santillán & Barraza (2015) showing no difference (Hedge’s g range: −0.13 to 0.09) in distance estimations based on their fatigue manipulation (treadmill running 2 min), whereas Jarraya et al (2013) found very large effect sizes following cycling for 10 mins (Hedge’s g range: 8.32 to 10.08), indicating participants estimated distances as closer in the post-exercise (fatigued) condition compared to the pre-exercise condition. Pooling of the studies’ similar distances (12 m and 11 m) was non-significant, with high heterogeneity (I 2 = 96%).…”
Section: Resultsmentioning
confidence: 99%
“…Two experiments used comparable distance measures, but in athletic populations ( Asaf, Santillán & Barraza, 2015 ; Jarraya et al, 2013 ). Asaf, Santillán & Barraza (2015) showing no difference (Hedge’s g range: −0.13 to 0.09) in distance estimations based on their fatigue manipulation (treadmill running 2 min), whereas Jarraya et al (2013) found very large effect sizes following cycling for 10 mins (Hedge’s g range: 8.32 to 10.08), indicating participants estimated distances as closer in the post-exercise (fatigued) condition compared to the pre-exercise condition. Pooling of the studies’ similar distances (12 m and 11 m) was non-significant, with high heterogeneity (I 2 = 96%).…”
Section: Resultsmentioning
confidence: 99%
“…Esto se debe a que el cuerpo necesita un tiempo para acostumbrarse al movimiento, especialmente cuando hay una asincronía entre la información interoceptiva y exteroceptiva. Coincidente con trabajos anteriores (Durgin et al, 2005), encontramos que un tiempo de adaptación de dos minutos corriendo a la velocidad empleada en la medición (nosotros utilizamos sobre todo 4 y 8 Km/h) era suficiente para lograr la adaptación, tanto en atletas como en no-atletas (Asaf, Santillán, & Barraza, 2014).…”
Section: La Cinta De Correr Como Plataforma De Investigaciónunclassified